Listen Up! Be Responsible! What Graduate Students Hear About University Teaching, Graduate Education and Employment - Aspenlieder, Erin; Vander Kloet, Marie (Canadian Journal of Higher Education, 2014)
What we hear at universities and in public conversations is that there is a crisis in graduate student education and employment. We are interested here in the (re)circulation of the discourses of crisis and responsibility. What do graduate students hear about their education, their career prospects, and their responsibilities? How does work in educational development contribute to these conversations? We explore these questions through an analysis of two data sets: the course outlines for multidiscipline graduate courses on university teaching, and popular and academic press articles on graduate education and employment. Through this discursive analysis, we first examine what graduate students hear through these two archives of writing. We then unpack two key discourses that emerge across the archives: the privileging of practice over theory, and the desire to assign responsibility for how the crisis of graduate education and employment should be resolved and by whom.